2011
DOI: 10.1186/1479-5876-9-65
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord blood-derived mononuclear cell transplantation: case series of 30 subjects with Hereditary Ataxia

Abstract: BackgroundThe differential diagnosis for hereditary ataxia encompasses a variety of diseases characterized by both autosomal dominant and recessive inheritance. There are no curative treatments available for these neurodegenerative conditions. This open label treatment study used human umbilical cord blood-derived mononuclear cells (CBMC) combined with rehabilitation training as potential disease modulators.Methods30 patients suffering from hereditary ataxia were treated with CBMCs administered systemically by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
(33 reference statements)
0
22
0
Order By: Relevance
“…However, to our knowledge there are only two studies using HuUCBCs for the treatment of CA [39, 40]. By using an anti-HLA-ABC antibody, we found that intravenous administered HuUCBMCs reached the cerebellum and brain stem of 3-AP-lesioned rats.…”
Section: Discussionmentioning
confidence: 79%
“…However, to our knowledge there are only two studies using HuUCBCs for the treatment of CA [39, 40]. By using an anti-HLA-ABC antibody, we found that intravenous administered HuUCBMCs reached the cerebellum and brain stem of 3-AP-lesioned rats.…”
Section: Discussionmentioning
confidence: 79%
“…There was a significant improvement in the Berg Balance Scale after 4 --6 weeks of treatment with intravenous and intrathecal human umbilical cord mononuclear cells and rehabilitation training in 30 patients with different hereditary ataxias (5 with SCA3/MJD) [90]. In a further study, 16 patients with SCAs (7 with SCA3/MJD) were treated with intravenous and intrathecal mesenchymal umbilical cord stem cell.…”
Section: Stem Cell Therapymentioning
confidence: 98%
“…No serious adverse hematological, biochemical or immunological effects were reported. Later, researchers reported significant improvements (>50%, Berg Balance Scale) after 4e6 combined intrathecal/intravenous infusions of allogeneic UCB cells in 13 of 30 patients with hereditary ataxia; in 17 other patients, the effect was smaller (5e49%) [39].…”
Section: Discussionmentioning
confidence: 97%